CADD Studies in the Discovery of Potential ARI (Aldose Reductase Inhibitors) Agents for the Treatment of Diabetic Complications - Gupta, Saurabh Kumar; Tripathi, Pushpendra Kumar (Current Diabetes Reviews, 2023)
The lack of currently available drugs for treating diabetes complications has stimulated our interest in finding new Aldose Reductase inhibitors (ARIs) with more beneficial biological properties. One metabolic method uses aldose reductase inhibitors in the first step of the polyol pathway to control excess glucose flux in diabetic tissues. Computer-aided drug discovery (CADD) is key in finding and optimizing potential lead substances. AR inhibitors (ARI) have been widely discussed in the literature. For example, Epalrestat is currently the only ARI used to treat patients with diabetic neuropathy in Japan, India, and China. Inhibiting R in patients with severe to moderate diabetic autonomic neuropathy benefits heart rate variability. AT-001, an AR inhibitor, is now being tested in COVID-19 to see how safe and effective it reduces inflammation and cardiac damage. In summary, these results from animal and human studies strongly indicate that AR can cause cardiovascular complications in diabetes. The current multi-center, large-scale randomized human study of the newly developed powerful ARI may prove its role in diabetic cardiovascular disease to establish therapeutic potential. During the recent coronavirus disease (COVID-19) outbreak in 2019, diabetes and cardiovascular disease were risk factors for severely negative clinical outcomes in patients with COVID19. New data shows that diabetes and obesity are among the strongest predictors of COVID-19 hospitalization. Patients and risk factors for severe morbidity and mortality of COVID- 19.
Keywords: polyol pathway